Answer:
Below.
Step-by-step explanation:
Substitute x = 3 into each polynomial and see if the value of the polynomial is zero. If it is zero then x-3 is a factor.
Try number 1:
a(x) = x^3 - 2x^2 - 4x + 3
a(3) = 3^3 - 2(3)^2 - 4(3) + 3
= 27 - 2(9) - 12 + 3
= 27 - 18 - 12 + 3
= 9 - 18 - 9
= 27 - 27
= 0
So a(x) has (x-3) is a factor of a(x)
The other 3 polynomials are solved in the same way.
-9v-6+7v=6
-2v-6=6
-2v=6+6
-2v=12
v=-6
Answer:
potanginaaaa you ahahahaha plss
Step-by-step explanation:
pa brainliest po baby bago Po Ako dito
Answer:
Step-by-step explanation:
1) ∠1 + ∠2 = 180 {linear pair}
105 +∠2 = 180
∠2 = 180 - 105
∠2 = 75°
Reason: Linear pair
2) ∠3 = ∠1 {Vertically opposite angles are congruent}
∠3 = 105
Reason: Vertically opposite angles are congruent
parallel means same slope. m = 2
y - y₁ = m(x - x₁)
y - (-11)= 2(x - (-3))
y + 11 = 2(x + 3)
y + 11 = 2x + 6
<u> -11 </u> <u> -11 </u>
y = 2x - 5
Answer: A